Diagnosis and management of binge eating disorder - BULIK, CYNTHIA M (Masson Italy, 2007)
This paper addresses current issues regarding the diagnosis and management of binge eating disorder (BED). Controversies in diagnosis include the lack of empirically validated criteria, the lack of a universally recognized operational definition of a "binge episode", and the lack of age-appropriate assessment instruments in light of growing reports of BED among children and adolescents. For adults with BED, several pharmacological and behavioral treatments have shown promise in reducing binge frequency and related psychological symptoms of disordered eating (i.e., disinhibition, hunger, depressed mood). Second-generation antidepressants and cognitive behavioral therapy are among the most widely studied treatments. However, no behavioral interventions have demonstrated efficacy with respect to weight loss (which is a critical concern for many BED sufferers who are overweight). Furthermore, randomized controlled trials for BED have been plagued by high drop out and placebo response rates, as well as by insufficient follow-up after active treatment ends to determine long-term outcomes. Therefore, the long-term utility of the various intervention strategies studied thus far remains unclear. More research is needed on innovative medications and behavioral treatments that explore novel modalities to reduce the subjectively reinforcing properties of binge eating. In addition, expanded use of information technologies may be particularly instrumental in the treatment of patients who experience marked shame, denial, and interpersonal deficits, or who face limited access to specialty care. Ultimately, examining BED within the broader context of the current obesity epidemic will be an important area of study.